Brick walls or brick columns? : management responses to the challenge of sustainability in community radio with special reference to Bush Radio and Radio Zibonele - Mati, Shepherd A. (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil) -- University of Stellenbosch, 2001.